Medically unexplained symptoms in children and adolescents: Illness-related self-concept and parental symptom evaluations - Jungmann, Stefanie M.; Witthöft, Michael (Journal of behavior therapy and experimental psychiatry, 2020)
According to cognitive-behavioral models, illness-related symptom evaluations and self-concepts play a pivotal role in the development and maintenance of medically unexplained somatic symptoms (MUS). However, illness-related cognitions related to MUS have rarely been studied in children/adolescents and their parents. Seventy-eight children and adolescents (M = 14.2 years; 59% female) performed two versions of the Implicit Association Test (IAT) to measure the implicit illness-related and the implicit anxiety-related self-concept. Illness-related evaluations of unspecific symptoms were assessed via the Health Norms Sorting Task (HNST), and MUS as well as characteristics of somatic symptom disorder (SSD) via questionnaires. MUS were significantly positively associated with the explicit (r = 0.30, p < .01) and implicit illness-related self-concept (r = 0.24, p = .04), but not with the anxiety-related self-concept (r = 0.15, p = .18). The implicit illness-related self-concept explained incremental variance in MUS (ΔR2 = 0.05, p = .04) beyond the explicit illness-related self-concept. Regarding health anxiety, parental illness-related symptom evaluations moderated the relationship between child-reported severity of MUS and health anxiety (B = 0.12, p < .01). Some measures have been adapted for childhood and adolescence, but validations on larger samples are still pending. A disorder-specific self-concept of being ill, as well as parental symptom evaluations, seem to play an essential role in MUS and health anxiety in childhood and adolescence. Due to the importance of the top-down processes found here, the findings are in line with current predictive coding models of somatic symptom perception. •Medically unexplained somatic symptoms (MUS) are common in children and adolescents.•In children/adolescents, MUS are associated with an illness-related self-concept.•How parents evaluate symptoms is associated with children's health anxiety.•Findings are in line with predictive-processing approaches to symptom perception.